Forgotten first responders: Australian surf lifesavers and lifeguards. (2nd March 2021) - Fien, Samantha; Lawes, Jasmin C; de Terte, Ian; Simon, Pamela; Joseph, Nancy; Daw, Shane; Drummond, Murray; Best, Talitha; Stanton, Robert
Abstract: First responders often face traumatic and emotionally‐taxing incidents in their role. Understanding their mental health and coping capacity is important for wellbeing and continued service delivery. Surf lifesavers and lifeguards are an under researched yet a vital part of the first responder workforce. The recent Senate Report on first responders explored mental health in the leading emergency services personnel in Australia and found a high incidence of mental health difficulties in those who worked or volunteered as emergency responders. However, a significant literature gap exists regarding mental health of surf lifesavers and lifeguards in both the international and Australian context. Here we propose a strategy to address this gap, at the individual, organisational and community level.